Estado nutricional e perfil clínico laboratorial de pacientes em tratamento hemodialítico - Bertoni, Vanessa Maria (2016)
Introduction: Chronic kidney disease is a public health problem due to the high rates of morbidity and mortality. In this way, characterizing the nutritional profile of these patients allows early diagnosis of possible nutritional risks. Objective: To evaluate the nutritional status of hemodialysis patients. Material and Method: A cross-sectional study performed at a Hemodialysis (HD) clinic from February to April 2016. Patients 18 years of age or older in HD for at least three months, who were able to respond to the evaluation, were included. Were able to perform a Bioimpedance test (BIA) and that they consented to participate. Nutritional status was determined by Body Mass Index (BMI). The Palmar Hold Force (FPP) was measured by dynamometer and the Adductor Muscle Thickness of the Thumb (EMAP) per adipometer, food intake was analyzed by means of a 24-hour Food Recall on days with and without HD and on weekday. A Global Subjective Evaluation (SGA) was performed adapted for renal patients. Biochemical data on urea, creatinine, kt / v, hemoglobin, hematocrit, transferrin, ferritin, iron, potassium, calcium, phosphorus, PTH, TGP, total cholesterol, LDL cholesterol, HDL cholesterol, glycemia and triglyceride Of patients. Results: Of the 33 patients, 66.7% were males, mean age 57.6 ± 14.2 years. The HD time ranged from 4 to 90 months. According to the BMI, eutrophy was prevalent (54.5%), followed by overweight (24.2%), some obesity (15.2%) and low weight (6.1%), 15.2% Of patients fit the diagnostic criteria for metabolic syndrome. On the other hand, EMAP showed significant muscle loss with severe depletion (66.7%), moderate depletion (24.2), mild depletion (3.0%). The FPP classified 72.7% of the patients as malnourished. Body Fat (CG), obtained through BIA, was high in 57.6%, adequate in 39.4% and low in 3% of the patients. Global Subjective Assessment adapted for HD rated 87.9% of the pati ents as mild malnutrition and 3% as moderate malnutrition. According to the Food Recall of 24 hours, the average caloric total was 1493 ± 530 Kcal, divided into 17.3% protein, 56.2% carbohydrate and 25.1% lipids. The protein mean was 0.88 ± 0.4 g / kg, there was no statistically significant difference in intake between the different days analyzed. Regarding diuresis, of the 81.8% of the patients presenting it, the median was 500ml | 300; 1000 | With statistically significant correlation (p = 0.009) with HD time. There was a statistically significant correlation between BMI and creatinine (p = 0.55), pre HD urea (p = 0.02) and protein (0.011). HD time correlated statistically with diuresis volume (p = 0.009), post-HD urea (p = 0.005), hematocrit (0.048). Conclusion: The study allowed to know the socio-demographic profile of the patients, to visualize biochemical and nutritional changes, food intake below the recommended level and different classifications of nutritional status depending on the method used. Thus, a comprehensive evaluation is important, involving biochemical data since they are more sensitive than other methods, and with this, a better nutritional monitoring and planning avoiding greater complications to the patient.